12.6k views
4 votes
Cooommmon guys help!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!plz

Cooommmon guys help!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!plz-example-1
User Osbert
by
6.4k points

2 Answers

4 votes

Answer:

D. y + 3 = -12/7(x - 5)

Explanation:

(5, -3) and (-2, 9)

slope = m = (9 - (-3))/(-2 - 5) = 12/(-7) = -12/7

Point slope form of the equation of a line:

y - y1 = m(x - x1)

We have slope = m = -12/7. We will use point (5, -3), so x1 = 5, and y1 = -3.

y - (-3) = -12/7(x - 5)

y + 3 = -12/7(x - 5)

User Aleation
by
5.4k points
2 votes

The point-slope form:


y-y_1=m(x-x_1)\\\\m=(y_2-y_1)/(x_2-x_1)

We have the points (5, -3) and (-2, 9). Substitute:


m=(9-(-3))/(-2-5)=(12)/(-7)=-(12)/(7)\\\\y-(-3)=-(12)/(7)(x-5)\\\\\boxed{y+3=-(12)/(7)(x-5)}

User Tomaz Fernandes
by
5.5k points